Building Superior Performance with Synergy of Work Discipline, Organizational Culture, and Employee Creativity - Jidan, Ammar (PRODUKTIF: Jurnal Kepegawaian dan Organisasi, 2023)
Basically, human resources have an important role in every aspect of an organization's life, including government organizations. The purpose of this study is to determine the influence of the influence of work discipline, organizational culture and creativity on the performance of employees of the Office of the Meteorology, Climatology and Geophysics Agency. This research method is associative type with quantitative approach. The study population in question is all employees working at the Office of the Meteorology, Climatology and Geophysics Agency which amounts to 158 people. The sample in this study amounted to 113 respondents. Data collection techniques by means of questionnaires, and data analysis techniques using instrument tests, classical assumption tests, regression analysis, coefficient of determination, tcalculate tests and Fcalculate tests with the help of SPSS 26 Software. The results showed that the results of the hypothesis test obtained a value of Fcalculate > Ftable or 58.963 > 2.69 with a value of Sig. 0.000 < 0.05. So H0 is rejected and H4 is accepted, and it can be concluded that simultaneously the variables of Work Discipline, Organizational Culture and Creativity have a significant effect on Employee Performance at the Head Office of the Meteorology, Climatology and Geophysics Agency.